Submission of a Civil Suit by a Prosecutor in the Interests of a State as a Way of Compensation for Damage, Caused by a Criminal Offence - Brusakova, Oksana Valeriivna; Shayturo, Olga Pavlivna; Simonovych, Davyd; Kuzubova, Tetiana (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The outcome of every trial is always accompanied by some interest where the civil attains compensation and the criminal imprisonment and fines. In achieving the said interest in a trial process, it is the role of the prosecutor in establishing that the accused is guilty of the crime committed. This article articulates, that it is the role of the prosecutor to carry out justice in the name of the State whether during the criminal or civil trial. The principle is clear here as we all know that during criminal proceedings the prosecutor is the principal party, but such a trial cannot succeed if in the course of the criminal act the victim also incurred damages caused by the accused. In this regard, it is also the role of the prosecuting counsel to submit such a civil action that has caused damages to the victim. There are lots of complexities surrounding the understanding and interpretation of the word